Antibiotic content of selective culture media for isolation of Capnocytophaga species from oral polymicrobial samples. (20th June 2013) - Ehrmann, E.; Jolivet‐Gougeon, A.; Bonnaure‐Mallet, M.; Fosse, T.
Abstract : Abstract: In oral microbiome, because of the abundance of commensal competitive flora, selective media with antibiotics are necessary for the recovery of fastidious Capnocytophaga  species. The performances of six culture media (blood agar, chocolate blood agar, VCAT medium, CAPE medium, bacitracin chocolate blood agar and VK medium) were compared with literature data concerning five other media (FAA, LB, TSBV, CapR and TBBP media). To understand variable growth on selective media, the MICs of each antimicrobial agent contained in this different media (colistin, kanamycin, trimethoprim, trimethoprim–sulfamethoxazole, vancomycin, aztreonam and bacitracin) were determined for all Capnocytophaga species. Overall, VCAT medium (Columbia, 10% cooked horse blood, polyvitaminic supplement, 3·75 mg l −1 of colistin, 1·5 mg l −1 of trimethoprim, 1 mg l −1 of vancomycin and 0·5 mg l −1 of amphotericin B, Oxoid, France) was the more efficient selective medium, with regard to the detection of Capnocytophaga species from oral samples ( P  <   0·001) and the elimination of commensal clinical species ( P  <   0·001). The demonstrated superiority of VCAT medium, related to its antibiotic content, made its use indispensable for the optimal isolation of Capnocytophaga species from polymicrobial samples. Significance and Impact of the Study: Isolation of Capnocytophaga species is important for the proper diagnosis and treatment of the systemic infections they cause and for epidemiological studies of periodontal flora. We showed that in pure culture, a simple blood agar allowed the growth of all Capnocytophaga species. Nonetheless, in oral samples, because of the abundance of commensal competitive flora, selective media with antibiotics are necessary for the recovery of Capnocytophaga  species. The demonstrated superiority of VCAT medium made its use essential for the optimal detection of this bacterial genus. This work showed that extreme caution should be exercised when reporting the isolation of Capnocytophaga species from oral polymicrobial samples, because the culture medium is a determining factor. Abstract : Significance and Impact of the Study: Isolation of Capnocytophaga species is important for the proper diagnosis and treatment of the systemic infections they cause and for epidemiological studies of periodontal flora. We showed that in pure culture, a simple blood agar allowed the growth of all Capnocytophaga species. Nonetheless, in oral samples, because of the abundance of commensal competitive flora, selective media with antibiotics are necessary for the recovery of Capnocytophaga  species. The demonstrated superiority of VCAT medium made its use essential for the optimal detection of this bacterial genus. This work showed that extreme caution should be exercised when reporting the isolation of Capnocytophaga species from oral polymicrobial samples, because the culture medium is a determining factor.